Stimulating Long-Term Growth and Welfare in the U.S. - James Malley; Apostolis Philippopoulos; Jim Malley (Center for Economic Studies and ifo Institute (CESifo), 2023)
We develop an endogenous growth model to quantify how permanent structural policy changes that enhance the fiscal policy mix, markets' functioning, and public institutions' quality affect long-term growth and welfare. The reforms include increased public investment, reduced market power through lower price markups for patents and intermediate goods, and an improved institutional framework that reduces rent-seeking. All reforms, except lower patent prices, lead to per-capita output and welfare gains along the transition and balanced growth paths. In contrast, a lower markup in the research sector hurts innovation, leading to lower growth over both paths and welfare losses along the transition.
Keywords: H30; O41; O43; 330; endogenous growth; structural policy; welfare